National scientific production on Burnout Syndrome in ICU nurses and physicians: a bibliometric study - Azevedo,Kely Cristina Carneiro de (2019)
SUMMARY OBJECTIVE: To analyze the scientific production on Burnout Syndrome in physicians and nurses of ICU in Brazil. METHOD: Bibliometric study, documentary, with quantitative approach. We selected articles published in Brazil on Burnout Syndrome in the ICUs, in the VHL and Portal Capes, from 2000 to 2018. RESULTS: 40 articles were identified, predominantly from the Southeast. Prevalence of those published in the Brazilian Journal of Intensive Care and in the Journal of Nursing UFPE online. The B2 Qualis periodical is the most prominent. The most prevalent descriptors were: Intensive Care Units, Burnout Syndrome, Burnout and Professional Exhaustion. CONCLUSIONS: Nurses are more interested in publishing this issue. Burnout Syndrome studied in intensive physicians would contribute to identifying its prevalence in these professionals.